A Grid‐group Analysis of Tourism Motivation. (22nd August 2013) - Li, Mimi; Zhang, Hanqin; Xiao, Honggen; Chen, Yong
Abstract Marketing theorists have widely proposed that culture is one of the underlying determinants of consumer behavior and that increasing globalization is creating a multicultural marketplace. Empirical inquiries in the field of tourism remain scarce, particularly regarding the understanding of behavioral influences. This study aims to fill this gap by investigating the influence of sub‐cultures on tourism motivation. Drawing on grid‐group cultural theory, an analysis of survey data from 727 Chinese tourists reveals that respondents classified as different cultural types had different travel motivations. Contributions and limitations of the study are discussed, and future research directions are suggested. Copyright © 2013 John Wiley & Sons, Ltd.